The success criteria of facilitators involved in community-based satellite distance education - Van Aswegen, Suzanne L.(Suzanne Laetitia) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1998.